Acute caffeine ingestion improves sport-specific and cognitive performance in elite badminton athletes - Feng, Liang; Du, Weiping; Wang, Xiaoting; Cao, Hui; Ji, Zhe; Li, Fang; Cao, Jianming; Zhou, Zhihui (Frontiers in Nutrition, 2025)
BackgroundCaffeine, a widely used central nervous system stimulant, has been extensively studied for its potential to enhance exercise performance. However, systematic evaluations of its effects on badminton-specific performance remain limited, particularly in the domains of cognitive function and technical skills.PurposeThis study aimed to evaluate the acute effects of caffeine ingestion on cognitive, physical, and technical performance in elite badminton players.MethodsA randomized, double-blind, placebo-controlled crossover design was employed. Fifteen elite male badminton players holding a national first-class athlete certificate participated. Each ingested either caffeine (5 mg/kg body mass) or a placebo, followed by a 45-min absorption period and a 50-min standardized fatigue protocol. Participants then completed badminton-specific performance tests, including the Anticipation Skills Test (AST), Smash Accuracy Test (SAT), Shuttle Run Agility Test (SRAT), and Repeated Sprint Test (RST). A 7-day washout period was applied between conditions.ResultsSignificant treatment × time interaction effects were observed for anticipation accuracy (F = 4.992, p = 0.029), reaction time (F = 4.084, p = 0.048), and visual search frequency (F = 8.514, p = 0.005), indicating improved post-fatigue performance in the caffeine condition, whereas the placebo condition declined or remained unchanged. In terms of physical performance, the caffeine group demonstrated superior overall agility in the SRAT (F = 4.097, p = 0.048) and showed an anti-fatigue effect in the RST (F = 5.283, p = 0.025). However, caffeine ingestion did not significantly affect smash accuracy (p = 0.942) or ratings of perceived exertion (RPE; p = 0.917).ConclusionAcute ingestion of 5 mg/kg caffeine significantly enhanced cognitive and physical performance under fatigue in elite badminton players, while exerting no apparent effect on fine technical skills.